Assistance The Importance Of Brand Awareness Home Industry "MAYA" In Lumajang - Budiwati, Hesti (IMPOWERMENT SOCIETY, 2020)
Home Industry is the smallest unit in a series of existing types of business, where household industries are generally managed independently as a family with the aim of increasing household income. The challenges for this home industry are also not easy. In general, because it is managed in a family environment or in one's own household, sometimes the management tends to be careless and mixed up between family finances and business finances. Starting from this reason, there is an interest in partnering with Hj's home industry salted egg "Maya". Umi Pristiwani in Jogotrunan Village, Lumajang Regency. Partners run their businesses whose main purpose is to help their families' economies. However, until now this partner has only been running his business as he is and has no brand, which means that he does not have a product identity but has a strong desire to move forward. Often partner businesses lose out in competing with other similar businesses. Partners are also not yet able to run their businesses that can create jobs for the surrounding community. The implementation of this community service activity achieves targets, namely (1) building understanding and awareness of the importance of brands for salted egg products, (2) improving partners' skills in running their businesses in a sustainable manner, (3) establishing understanding and the ability of human resources in creating jobs for the surrounding community, and (4) increasing marketing strategies so that they are able to compete in marketing their products. Intensive assistance and supervision to program partners needs to be carried out periodically and does not stop until the completion of this program, therefore the activity of the team and the staff of STIE Widya Gama Lumajang in providing guidance to these partners needs to be carried out on an ongoing basis.